Proyecto de Factibilidad para la Creación de una Caja de Ahorro, en la Parroquia Taquil, Cantón Loja, Provincia de Loja. - Quizhpe Cuenca, Dayanna de los Ángeles (2024)
The main purpose of the Feasibility Project for the Creation of a Savings Bank in the Taquil Parish, Canton Loja, Loja Province is to provide information to determine the feasibility of creating a savings bank in the Taquil parish, which would help the inhabitants of the parish to save and finance their savings. A market study was carried out, for which a survey was applied to the inhabitants of the parish, through which it was determined a demand of 263 people who would be part of the savings bank. The appropriate location for the savings bank is in the facilities of the parish council of the Decentralized Autonomous Government of Taquil, and the process of the service and the technical requirements for its operation are also designed. In the financial study, the total investment and financing of the project was determined, as well as the budget that will be available for this investment. In the financial evaluation, it was determined that the project is feasible according to the following indicators: Net Present Value (NPV), a positive value of $16,705.26 was obtained.705.26, likewise the Internal Rate of Return (IRR) was established at 16.36%, which means that the project is feasible, likewise for the Benefit-Cost Ratio (BCR) a positive value of $4.11 was obtained, that is, the savings bank for each dollar invested will have a benefit of $3.11 cents of profitability, on the other hand, with respect to the Capital Recovery Period (CRP) it is observed that the project will recover its investment of $128.334.92 in the period of 4 years, 3 months and 6 days, which results in a considerable time of economic life of the project, it is concluded that the project is feasible and it can be executed so it is recommended the creation of the savings bank in the parish Taquil of the province of Loja, since thanks to the above mentioned aspects are positive and they ensure profitability.